Redeeming masculinity a Catholic theology of masculinity - Holmes, Peter D. (Pickwick Publications, 2024)
"John Paul II spoke of a feminine genius, using the phrase to describe the unique and positive contribution of women to relationships, the church, and society. What of men? There is considerable debate regarding the nature, roles, and responsibilities of men. What does the church have to say to a boy or young man searching for guidance in developing a genuinely Christian manhood? Or to parents, schools, and communities seeking to cultivate this in their young men? Or to the faithful seeking to understand the church's teachings and to apply these in public and private life? This book seeks to answer the question: Is there a masculine genius? Is there a unique and positive contribution men bring to relationships, the church, and society?" -- Back cover
Keywords: Männlichkeit; Katholische Theologie; Masculinity / Religious aspects / Catholic Church; Sex role / Religious aspects / Catholic Church